Phagomimetic action of antibiotics: revisited. How do antibiotics know where to go? - Gutteridge,JMC; Quinlan,GJ; Kovacic,P (Biochemical and Biophysical Research Communications, 2020)
Phagocytic cells know exactly where an infection is by following chemotactic signals. The phagocytosis of bacteria results in a 'respiratory burst' in which superoxide radicals are released. We have previously compared the release of reactive oxygen species (ROS) by antibiotics, during electron transfer reactions, to this event. Antibiotics in their normal bacterial environment, and ROS, are both increasingly implicated in purposeful signalling functions, rather than their more widely known roles in bacterial killing and molecular damage. Here, we extend our comparison between antibiotics and phagocytic cells to propose that antibiotics actively accumulate at a site of pathogen infection or tumour growth. A common link being virulent cellular growth. When this occurs, new proteins are secreted, aberrant iron acquisition takes place, and lipocalins are released. Each provide a mechanism by which antibiotics can bind, and be retained, at an active site of pathogen infection or tumour growth.